Constructing the ideal victim in the United States of America’s annual trafficking in persons reports - Wilson, Michael (Crime, law and social change, 2016)
Human trafficking as a global phenomenon continues to elude accurate quantitative measure, and remains a controversial policy domain significantly influenced by anecdotal evidence. Drawing on the policy analysis framework of Bacchi (1999, Policy and Society, 26(3), 5-20, 2007) the problem representation of trafficking through narratives can be considered a direct antecedent of contemporary anti-human trafficking policy. This article explores the construction of human trafficking within the Trafficking in Persons Reports, published annually by the United States of America’s Department of State. An examination of the victim and offender narratives contained within the reports published between 2001 and 2012 demonstrates that human trafficking is predominantly represented as a crime committed by ideal offenders against idealized victims, consistent with Christie’s (1986) landmark criteria of ideal victimization. This representation of an ideal prototype has the potential to inform policy that diverts focus from the causative role of global socioeconomic injustice towards criminal justice policies targeting individual offenders.